2008
DOI: 10.1088/0029-5515/49/1/015003
|View full text |Cite
|
Sign up to set email alerts
|

Plasma behaviour at high β and high density in the Madison Symmetric Torus RFP

Abstract: Pellet fuelling of improved confinement Madison Symmetric Torus (MST) plasmas has resulted in high density and high plasma beta. The density in improved confinement discharges has been increased fourfold, and a record plasma beta (βtot = 26%) for the improved confinement reversed-field pinch (RFP) has been achieved. At higher β, a new regime for instabilities is accessed in which local interchange and global tearing instabilities are calculated to be linearly unstable, but experimentally, no severe effect, e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 42 publications
5
25
1
Order By: Relevance
“…Some of the key parameters from these plasmas are shown in table 1. Recent work from the MST [15] and RFX-mod [34] experiments has demonstrated that the Greenwald density limit for tokamaks [35] applies to these two RFP devices as well. This limit on the line-averaged electron density = I φ /π a 2 , where I φ is the toroidal plasma current in megaamperes, a is the plasma minor radius in metres, and the density limit is in units of 10 20 m −3 .…”
Section: Improved Confinement At Higher Density and High Betamentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the key parameters from these plasmas are shown in table 1. Recent work from the MST [15] and RFX-mod [34] experiments has demonstrated that the Greenwald density limit for tokamaks [35] applies to these two RFP devices as well. This limit on the line-averaged electron density = I φ /π a 2 , where I φ is the toroidal plasma current in megaamperes, a is the plasma minor radius in metres, and the density limit is in units of 10 20 m −3 .…”
Section: Improved Confinement At Higher Density and High Betamentioning
confidence: 99%
“…In other discharges with current profile control, we have quadrupled the plasma density with injection of deuterium pellets [14,15]. Core and edge fluctuations are reduced, energy confinement is improved and the ion temperature rises along with the electron temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmas are created in an aluminum torus with a major radius of 1.5 m (R 0 ), a minor radius of 0.52 m (a), and a thickness of 0.05 m. 10,15,17 The torus acts as the vacuum vessel, the conducting shell and the toroidal field winding (single turn). Discharges can have plasma currents from 200 to 600 kA and electron densities on the order of $10 13 cm À3 .…”
Section: Apparatus and Experimentsmentioning
confidence: 99%
“…Discharges can have plasma currents from 200 to 600 kA and electron densities on the order of $10 13 cm À3 . 15 MST discharges are typically deuterium plasmas lasting $70 ms with ion energies up to 40 keV (using neutral beam injection, NBI). 12 To make measurements on MST, the CNPA needed to be upgraded and calibrated for deuterium with ion temperatures between 0.1 and 2 keV.…”
Section: Apparatus and Experimentsmentioning
confidence: 99%
“…This system was developed to provide a flexible means of plasma fueling on a wide variety of magnetic confinement devices, at relatively low costs for installation and operations. The original prototype was installed on the Madison Symmetric Torus (MST) in early 2002 [5,6] and has since been used extensively in plasma experiments [6,[7][8][9]. This injector type is ideally suited for the TJ-II application [10,11].…”
Section: Introductionmentioning
confidence: 99%